Association between perceived chewing ability and oral health-related quality of life in partially dentate patients - Inukai, Mika (BioMed Central, 2010)
BACKGROUND: One of the most immediate and important functional consequences of many oral disorders is a reduction in chewing ability. The ability to chew is not only an important dimension of oral health, but is increasingly recognized as being associated with general health status. Whether perceived chewing ability and oral health-related quality of life (OHRQoL) are correlated to a similar degree in patient populations has been less investigated. The aim of this study was to examine whether perceived chewing ability was related to OHRQoL in partially dentate patients. METHODS: Consecutive partially dentate patients (N = 489) without signs or symptoms of acute oral disease at Tokyo Medical and Dental University's Prosthodontic Clinic participated in the study (mean age 63.0 ± 11.5, 71.2% female). A 20-item chewing function questionnaire (score range 0 to 20) was used to assess perceived chewing ability, with higher scores indicating better chewing ability. The 14-item Oral Health Impact Profile-Japanese version (OHIP-J14, score range 0 to 56) was used to measure OHRQoL, with higher scores indicating poorer OHRQoL. A Pearson correlation coefficient was calculated to assess the correlation between the two questionnaire summary scores. A linear regression analysis was used to describe how perceived chewing ability scores were related to OHRQoL scores. RESULTS: The mean chewing function score was 12.1 ± 4.8 units. The mean OHIP-J14 summary score was 13.0 ± 9.1 units. Perceived chewing ability and OHRQoL were significantly correlated (Pearson correlation coefficient: -0.46, 95% confidence interval [CI]: -0.52 to -0.38), indicating that higher chewing ability was correlated with lower OHIP-J14 summary scores (p < 0.001), which indicate better OHRQoL. A 1.0-unit increase in chewing function scores was related to a decrease of 0.87 OHIP-J14 units (95% CI: -1.0 to -0.72, p < 0.001). The correlation between perceived chewing ability and OHRQoL was not substantially influenced by age and number of teeth, but by gender, years of schooling, treatment demand and denture status. CONCLUSION: Patients' perception of their chewing ability was substantially related to their OHRQoL.